Content or context : which matters more in information processing on microblogging sites - Zhang, Lun (2014)
With a framework based on the heuristic-systematic model of information processing, this study examined the effects of both content and contextual factors on the popularity of microblogging posts. The popularity of posts was operationalized as the re-tweeting times and number of comments received by posts, which are users’ behavioral outcomes after processing information. The data of the study were 10,000 posts randomly drawn from a popular microblogging site in China. Content factors were found to outperform contextual ones in accounting for posts’ popularity, which suggests that systematic strategy dominates users’ information processing in comparison with heuristic strategy on microblogging sites. Our findings implied that re-tweeting and commenting are distinct types of microblogging behaviors. Re-tweeting aims to disseminate information in which the source credibility (e.g., users’ authoritativeness) and posts’ informativeness play important roles, whereas commenting emphasizes social interaction and conversation in which users’ experience and posts’ topics are more important.